Luciobarbus kottelati, a new species of barbel (Teleostei: Cyprinidae) from the Buyuk Menderes River, Turkey, with rediagnose of L. lydianus - Turan, Davut; Ekmekçi̇ F. Güler; İlhan Ali̇; Engi̇n Semi̇h (Zootaxa, 2008)
Luciobarbus kottelati, new species, is described from the River Büyük Menderes, Aegean Sea drainage, Turkey. It is distinguished from all other species of Luciobarbus in Europe and western Anatolia by the pelvic-fin origin markedly in front of the dorsal-fin origin (vs. behind). Luciobarbus lydianus, considered to be a synonym of L. pectoralis by most recent authors is a valid species and is rediagnosed.